The effects of the internationalization of universities in pre-service english teacher education - RAMOS, SAMANTHA MANCINI; Machado Brener, Fernanda; Belo, Areta Estefane (The ESPecialist, 2023)
This qualitative study analyzes the perceptions of future English teachers concerning the teaching of English for Specific Purposes (ESP) and the preparation to work in programs that promote the English language as an agent of internationalization in Brazilian universities. Data were collected from students’ participation in a webinar and in an online discussion forum. The results point to a gap in their pre-service training that disfavors their performance in English teaching contexts aimed at internationalization. Based on these conclusions, we present possibilities for improving internationalization practices and ESP teaching in the aforementioned training through the expansion of complementary academic activities, extension projects, internships and curriculum reformulation.